IDENTIFICATION OF THE CTX-M GENE IN KLEBSIELLA PNEUMONIAE PRODUCING ESBLS IN UTI PATIENTS AT A PRIVATE HOSPITAL IN PURWOKERTO, BANYUMAS REGENCY, CENTRAL JAVA - CROSS SECTIONAL STUDY - Kurniawan, Anang; Setyono, Joko; Utami Anjarawati, Dwi (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: The CTX-M gene in ESBLs-producing Klebsiella pneumoniae is associated with virulence factors and encodes for antibiotic resistance. There are currently 128 different varieties of CTX-M, which gene can hydrolyze beta-lactam medicines like cefotaxime. Purpose: Identify the CTX-M gene in Klebsiella pneumoniae from patients with Urinary Tract Infections (UTI) at a private hospital in Banyumas Region of Central Java, Indonesia. Method: Cross-sectional survey method was employed in this study. The subjects of the study comprised 40 patients with UTI admitted to a private hospital in Banyumas Region, Central Java, Indonesia. Using a direct molecular approach called Polymerase Chain Reaction (PCR) directed against the CTX-M gene, DNA was isolated from isolates cultured in CHROMagarTM ESBLs obtained from catheter urine samples. Result: A total of 4 out of 40 urine samples (10%) tested positive for ESBL-producing Klebsiella pneumoniae. The PCR was performed to detect the CTX-M gene in 100% of the strains. Conclusion: These findings suggest the presence of CTX-M gene found in ESBLs-producing Klebsiella pneumoniae in individuals with urinary tract infections in a private hospital in Purwokerto, Banyumas regency, Central Java, Indonesia. This information can be used to assess antibiotic administration practices.